2014
DOI: 10.1038/ncomms4008
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic focused reference beam X-ray holography

Abstract: Fourier transform holography is a highly efficient and robust imaging method, suitable for single-shot imaging at coherent X-ray sources. In its common implementation, the image contrast is limited by the reference signal generated by a small pinhole aperture. Increased pinhole diameters improve the signal, whereas the resolution is diminished. Here we report a new concept to decouple the spatial resolution from the image contrast by employing a Fresnel zone plate to provide the reference beam. Superimposed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 35 publications
(58 reference statements)
0
28
0
Order By: Relevance
“…In fact, if an accurate characterization of the reference wave is available, the ILRUFT method can be tailored to best use this information, potentially exceeding the performance of other methods. For example, the ILRUFT method could account for the aberrations of a Fresnel-zone plate reference 13 . It should be noted that other extended references, such as corner or URA references, impose requirements on the uniformity of reference composition and thickness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, if an accurate characterization of the reference wave is available, the ILRUFT method can be tailored to best use this information, potentially exceeding the performance of other methods. For example, the ILRUFT method could account for the aberrations of a Fresnel-zone plate reference 13 . It should be noted that other extended references, such as corner or URA references, impose requirements on the uniformity of reference composition and thickness.…”
Section: Discussionmentioning
confidence: 99%
“…However, adjacent pinholes must be sufficiently separated to produce non-overlapping holograms and consequently the field-of-view is used inefficiently. Alternatively, flux and resolution can be decoupled by using extended references 1,[11][12][13] . The image-reconstruction procedure for extended references involves the application of linear operators, such as convolution 1 , linear filters 11,12 or propagation 13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The field of view is usually restricted by an aperture, fabricated into an X-ray-opaque metal-film mask that is produced in close proximity to the sample substrate. The reference beam allowing for phaseencoding typically originates from a small pinhole adjacent to the object fabricated into the same mask [17], while the use of more complex reference beams is also possible [13,25]. This integrated mask design monolithically couples the source of the reference wave to the object to be imaged and generates the remarkable stability of FTH against drift and vibration during exposure.…”
Section: Theorymentioning
confidence: 99%
“…However, the holographic reconstruction of the wave field in the plane of the reference source allows to propagate the angular spectrum of the reconstruction [18,20] along the beam axis and thereby refocus specimen features outside the depth-of-field. It has been shown that the plane of least confusion can be separated from the plane of the reference by numerically propagating the reconstructed specimen wave front according to the physical separation between both planes [21,25]. Similarly, a thoroughly focused reconstruction of an extended 3D object can be obtained by numerically propagating the reconstructed wave fronts of individual object features outside the depth-of-field into focus.…”
Section: Theorymentioning
confidence: 99%